Setting Up Joint Ventures in China - Devonshire-Ellis, Chris; Scott, Andy; Woollard, Sam (China Briefing, The Practical Application of China Business4, 2011)
This brand new guide book is a comprehensive overview of establishing joint ventures in China. It details all applicable decision making processes such as assessing your potential partner, choosing the relevant JV structure, conducting legal and financial due diligence. The guide contains complete JV contract and articles of association as well as an overview of JV law, details negotiation issues, land use rights, IP Protection and technology transfer, in addition to tips on staff hiring and HR. It also describes the tax and audit responsibilities in addition to buying out a JV partner and liquidations. It is a concise, detailed yet pragmatic guide of use to anyone considering or owning a JV in China.